Results on the Exponential Integral - Zenku, T.; Jolevska-Tuneska, B. (Sarajevo Journal of Mathematics, 2017)
Results on the convolution product of the exponential integral and exponential function are given. These results are found in a space of distributions. The convolution products gained in this work may be considered as a generalization of Chandrasekhar's functions which are needed in the problem of diffuse reflections and transmission of radiation by an atmosphere.